1986
DOI: 10.1128/mcb.6.6.2257
|View full text |Cite
|
Sign up to set email alerts
|

Arginine-mediated regulation of an argininosuccinate synthetase minigene in normal and canavanine-resistant human cells.

Abstract: Regulation of argininosuccinate synthetase (AS) was studied by using minigenes containing 3 kilobases of DNA upstream from the TATAA box and 9 kilobases downstream (including the first four exons of the AS gene) ligated to either the cDNA for AS or to the chloramphenicol acetyltransferase (CAT) gene. Unlike the endogenous AS gene, expression of the CAT minigene was not elevated in Canrl cells, which overproduce AS compared with parental RPMI-2650 cells. Expression of the CAT minigene in both stable and transie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

1986
1986
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 9 publications
1
14
0
Order By: Relevance
“…sites [71]. The expression of ASS also has been showed to be regulated by arginine [72]. In this regard, we have demonstrated that in melanoma cell lines the expression of ASS is also influenced by arginine in media [18], but not influenced by either glutamine glucocorticoid or fatty acids (unpublished data).…”
Section: Why Ass Is Not Expressed In Certain Tumor Types ?mentioning
confidence: 59%
“…sites [71]. The expression of ASS also has been showed to be regulated by arginine [72]. In this regard, we have demonstrated that in melanoma cell lines the expression of ASS is also influenced by arginine in media [18], but not influenced by either glutamine glucocorticoid or fatty acids (unpublished data).…”
Section: Why Ass Is Not Expressed In Certain Tumor Types ?mentioning
confidence: 59%
“…The gene for human argininosuccinate synthase has been cloned and partially sequenced (13). The regulation of argininosuccinate synthase is mediated by a trans-acting molecule and the region of the gene required for the regulation is partially defined (14,15).…”
mentioning
confidence: 99%
“…Amplified PCR products were cloned into a pCR-II vector using theTA cloning system (Invitrogen) for further analysis. Double-stranded DNA was sequenced by the dideoxy chain-termination method using Sequenase (United States Biochemical) and 35S-labelled dATP [6,7,[9][10][11] and/or using the Hitachi model SQ-5500 DNA auto-sequencer by using ATaq fluorescent dye-primer cycle sequencing kit (Amersham) and Texas-red labelled primer.…”
Section: Differential Display Of Mrnamentioning
confidence: 99%
“…We can now diagnose 11 of 22 mutations in classical citrullinemia using genomic DNA by Southern blot analysis and by a combination of polymerase chain reaction (PCR) and restriction enzyme digestion ( [6,7,10,11]; Kakinoki et al, manuscript in preparation).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation